Identifikasi Motivasi Belajar dan Hasil Belajar Pendidikan Jasmani Kelas X SMA Negeri 11 Semarang Melalui Pembelajaran Cultularry Responsive Teaching (CRT) dan Teaching at The Right Level (TARL) - Panjilaksana, Susan Dicky Dewa; Pradipta, Galih Dwi; Darmanto, Purno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The purpose of this research is to identify the learning motivation and learning outcomes of physical education, sports and health subjects in grade X students of SMA Negeri 11 Semarang through a game learning model based on Cultularry Responsive Teaching (CRT) compared to Teaching at The Right Level (TARL). This research is categorized as a quantitative research that uses a survey design approach. The sampling technique applied is purposive sampling. The sample of this study is 62 students in class X.4 and class X.2. The instruments in this study used 2 instruments, namely questionnaires and tests. Descriptive statistics, and hypothesis tests are some of the analyses used in this study. The results of the study obtained information that in the aspect of motivation there was a difference in the average score of 4.83. The results of the differential test showed that the score of 0.001 was less than 0.05, meaning that there was a significant difference in learning motivation between the game learning group based on Cultularry Responsive Teaching (CRT) and the Teaching at The Right Level (TARL) learning model. Meanwhile, the learning outcomes differed in average score of 17.82. The result of the test with a score difference of 0.001 is less than 0.05, meaning that there is a difference in the learning outcomes of Cultularry Responsive Teaching (CRT) with the Teaching at The Right Level (TARL) learning model. learning motivation and learning outcomes of physical education, sports and health in grade X students of SMA Negeri 11 Semarang experienced significant differences from learning games based on Cultularry Responsive Teaching (CRT) with Teaching at The Right Level (TARL) learning. Learning motivation in the high category of Cultularry Responsive Teaching (CRT)-based game learning group and the teaching at The Right Level (TARL) learning model group of 63 are also included in the high category.